Connectivity and Functional Specialization in the Brain - Heinbockel, Thomas; Zhou, Yongxia (IntechOpen, 2021)
'Connectivity and Functional Specialization in the Brain' is a topic that describes nerve cells in terms of their anatomical and functional connections. The term connectome refers to a comprehensive map of neural connections, like a wiring diagram of an organism's nervous system. Connectomics, the study of connectomes, can be applied to individual neurons and their synaptic connections, as well as to connections between neuronal populations or to functional and structural connectivity of different brain regions. This book addresses neural connectivity at these various scales in health and disease. The chapters review novel findings related to neuroanatomy and cell biology, neurophysiology, neural plasticity, changes of connectivity in neurological disorders, and sensory system connectivity. The book provides the reader with an overview of the current state-of-the-art of research of neural connectivity and focuses on the most important evidence-based developments in this area. Individual chapters focus on recent advances in specific areas of neural connectivity and in different brain regions. All chapters represent recent contributions to the rapidly developing field of neural connectivity.